A new fibrin-heparine coated self-expanding stent for the rescue treatment of intracranial stenosis: a multicentric study - Dorn, Franziska; Möhlenbruch, Markus Alfred; Jesser, Jessica; Vollherbst, Dominik; Schob, Stefan (Clinical neuroradiology, 2025)
Introduction: Rescue intracranial stenting is necessary to provide sufficient recanalization after mechanical thrombectomy (MT) in patients with acute large vessel occlusions (LVO) due to an underlying intracranial atherosclerotic disease (ICAD). The CREDO heal is a novel stent that provides a potentially lower thrombogenicity due to surface modification. We present the first multicentric experience with the CREDO heal for acute rescue stenting. Methods: Data of 81 patients who underwent rescue stenting after MT at 12 centers in Germany and Spain were prospectively collected and retrospectively evaluated. Results: Final mTICI 2b‑3 was reached in 95.1% after median two MT maneuvers and stenting. Four periprocedural complications resulted in clinical deterioration (4.9%). Intraparenchymal hemorrhage occurred in one patient (1.2%) and functional independence at FU was reached by 42% of the patients. Most interventions were performed under Gp IIb/IIIa inhibitors. Conclusion: CREDO heal was effective and safe in our case series. However, more data is needed to define the optimal antithrombotic regime. The use under single antiplatelet medication is not supported by our study.
Gesehen am 24.02.2025